PENGARUH KELOMPOK REFERENSI, KELUARGA DAN KEPRIBADIAN TERHADAP PERILAKU KONSUMEN KARTU AS TELKOMSEL (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS JAMBI) - Sri Juliati (Jurnal Dinamika Manajemen, 2015)
Consumer Behavior of Kartu As Telkomsel, a case study on students of the Faculty of Economics, University of Jambi. The purpose of this study was to determine, test and analyze the influence of reference groups, family and personality on the consumer behavior of Kartu As Telkomsel. The method used to analyze the problem is to use multiple linear regression analysis and to do the F test and t test. The results of this study can be concluded that reference groups, family and personality have an influence on consumer behavior in using Telkomsel Ace cards. Simultaneously, the effect of these three factors is 9.6%. While partially, of the three factors, the reference group and personality factors provide the most dominant influence.